Sedation and need-free salt intake in rats treated with clonidine - De Luca, L. A.; De Souza, RLN; Yada, M. M.; Meyer, E. W. (Elsevier B.V., 1999)
The effect of intraperitoneal injection of clonidine (9-72 mu g/kg) on need-free 1.5% NaCl intake and on performance (defined as percent of a complete trial) in the rotarod test, was studied in normovolemic adult male rats. Clonidine (18 and 36 mu g/kg) inhibited the 1.5% NaCl intake in a 2-h test at doses that did not alter the performance in the rotarod test. The dose of 36 mu g/kg did not inhibit 10% sucrose intake. Only the highest dose (72 mu g/kg) of clonidine inhibited the 1.5% NaCl intake and the performance in the rotarod test, and produced signs of sedation. Sedation was determined either by change in posture (immobility or lack of postural tonus) of the animals during the ingestive test or by their performance in the rotarod test. The results suggest that sedation is not a determinant effect on the inhibition of 1.5% NaCl intake induced by clonidine. (C) 1999 Elsevier B.V.
Keywords: salt intake; sodium intake; water intake; food intake; sucrose; adrenoceptors; anxiolytics; rotarod